Adsorption of Methyl Orange and Cr (VI) Onto Poultry Manure-Derived Biochar From Aqueous Solution - Ghani, Usman; Jiang, Wenjia; Hina, Kiran; Idrees, Atif; Iqbal, Meenal; Ibrahim, Muhammad; Saeed, Rashid; Irshad, M. Kashif; Aslam, Imran (Frontiers in Environmental Science, 2022)
In recent years, heavy metals and other organic compound pollution has increased and become a considerable global problem due to its direct impacts on the aquatic ecosystem. This study is aimed to see how efficient the poultry manure-derived biochar is in removing chromium (VI) and methyl orange simultaneously from the aqueous solutions through adsorption. Chromium present in the form of reactive ions such as HCrO4− and Cr2O72− at pH 2–6 values and in stable form, CrO4− at alkaline pH. In this study, biochar was synthesized by the slow pyrolysis of feedstock in a muffle furnace at 550°C temperature with 2 mm particle size. This study provided the biochar with SBET 16.0921 m2/g rough stomata-like pores with a volume of 0.0074 cm³/g, pore diameter 1.84 nm, aromatic groups, and structural diversity. A batch adsorption experiment was conducted to investigate the adsorption efficiency, and mechanism was elucidated by fitting isotherm and kinetic models and result analysis along with the thermodynamics. From the linear Langmuir fit results the maximum adsorption capacity (qmax) of biochar reached up to 20.8 and 19.09 mg g−1 for MO and Cr, respectively. Different operational factors like reaction time, pollutant initial concentration, effect of temperature, and sorbent material dose were studied at pH 4 and initial concentration of 100 mg/L using 2 g of the adsorbent dose. The linear Langmuir well fitted with the experimental data having R2 value of 0.99 and 0.99 for MO and Cr, respectively. From the obtained results, the highest adsorption efficiency reached 88.80% and 90.231% for MO and Cr, respectively.From kinetics study, non-linear pseudo–second-order (PSO) model are highly fitted with the obtained data with R2 of 0.97 and 0.974 for MO and Cr, respectively. The result analysis revealed that HCrO4− and Cr2O72− ions compete with the SO3− to attach on the surface of the sorbent which leads to competitive adsorption of Cr (VI) and MO onto BC. Thermodynamic study presents that the change in Gibbs free energy ΔG° is negative, indicates that the whole process was favorable and completed. The adsorption process was monolayer physisorption, irreversible, and endothermic. Hence, it can be said that this material is environmental friendly and an economical sorbent for high adsorption efficiency.